The Effect of Water Depth on the Structure and Allocation of Waterlily (Nymphaea pubescens Willd) Biomass in Lebak Swampland in Kalimantan Selatan - ISMUHAJAROH, Bakti Nur; INDRADEWA, Didik; KURNIASIH, Budiastuti; UTAMI, Sri Nuryani Hidayah (Journal of Environmental Management and Tourism, 2022)
Nymphaea pubescens is found in the swamplands of Kalimantan Selatan, where it lives in the shape of a basin with divergent levels of water. From February to June 2019, the environment and its development were studied in four zones, with depth differences ranging from 28 to 95 meters in the zone I, 28 to 99 meters in zone II, 54 to 112 meters in zone III, and 55 to 124 meters in zone IV. A transect system is used to zone the area, with fluctuating degrees of water depth reflected in each zone as one moves closer to a basin. Geomorphology in a basin has an essential relief, causing different levels of water surface depth in lebak swampland. The GPS was used to determine the distance traveled. The purposive sampling technique determines the number of observation stations in each zone. In zone I, waterlily growth generated smaller and more frequent leaves than plants in zone II, which produced smaller and fewer leaves than plants in zone III, which produced smaller and fewer leaves than plants in zone IV. However, the area of the leaves expanded greatly with the depth of water, although the number of leaves fell dramatically with water depth. The organization of the percentage of biomass for the development of shoots and roots was different, even though the total biomass was not statistically different. Waterlily growing in shallower water depths had larger biomass allocations for seeds and lower biomass allocations for roots. Root biomass increased significantly as the depth of the water body increased. This experiment showed that the deeper the water, the lesser the nutrients and the greater the extent the roots must spread to meet their nutritional requirements. Even though the relationship between leaf area and bloom number weakened as water depth increased, the relationship between leaf number and root number was significantly positive concerning biomass and water depth. Groundwater depth has a significant effect on the allocation of underground biomass (A), with the biomass proportion decreasing as water depth increases from 28 to 95 cm in zone I = 53.1 percent to 28–99 cm in zone II = 53.7 percent to 55–124 cm in zone III = 48.6 percent in zone IV = 42.4 percent. Because water depth has a considerable effect on the average aboveground biomass–to–underground biomass ratio, the average root crown ratio decreases as water depth increases. Among the lowest average ratios found are those found at a water depth of 55–124 cm in zone IV (ratio of 0.54 ± 0.2), while the highest average percentage found is that found at a water depth of 28–95 cm in the zone I (ratio of 1.25 ± 0.61).